PENGARUH PENGGUNAAN AUGMENTED REALITY TERHADAP KEMAMPUAN LITERASI SAINS SISWA PADA METERI SISTEM PEREDARAN DARAH - Salsabila, Fahritsa; Bintang Ilhami, Fasih (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The development of science and technology (IPTEK) in the Industrial Revolution 4.0 era requires the world of education to adapt the learning process to the characteristics of digital technology-based learning and the development of students' scientific understanding. Learning that still uses conventional methods makes students tend to memorize without understanding complex concepts. Scientific literacy is an important competency in science education so that students are able to understand natural phenomena scientifically and think rationally in facing everyday life problems. Indonesian students' scientific literacy abilities are categorized as low. This study aims to examine the effect of using Augmented Reality media using the Think Pair Share (TPS) learning model on the scientific literacy abilities of students of Junior High School 48 Surabaya on the circulatory system material. This study uses a quantitative approach with an experimental method with a Pre-Experimental Design (non-design) research design of the One Group Pretest-Postest Design type. The results of the Wilcoxon Signed-Rank Test show the Asymp. value. (2-tailed) <0.001, so there is a significant difference between the Pretest and Posttest scores. It can be concluded that the integration of Augmented Reality with the Think Pair Share model is effective in improving students' scientific literacy through more visual, interactive learning and encouraging active involvement in the scientific thinking process.